2019
DOI: 10.1542/peds.2017-4156
|View full text |Cite
|
Sign up to set email alerts
|

Use of Social Psychology to Improve Adherence to National Bronchiolitis Guidelines

Abstract: OBJECTIVES:The American Academy of Pediatrics' bronchiolitis guidelines recommend against albuterol and corticosteroids for treating and chest radiographs (CRs) for diagnosing infants with bronchiolitis. However, high rates of nonadherence have been documented. Our objective was to improve guideline adherence in infants with bronchiolitis.METHODS: This quality improvement study was conducted in 1 urban academic pediatric primary care clinic caring for predominately minority and publicly insured children. We te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…After education in our initiative, CDT entry increased and peaked at ∼60%; however, declines were observed within 6 months. In particular, although past research suggests that public reporting of individual performance might be an effective method to motivate provider behavior change, 30,31 this was not observed in our study. Instead, we observed that public auditing and reporting of attending-provider performance was associated with essentially static levels of CDT use.…”
Section: Discussioncontrasting
confidence: 91%
“…After education in our initiative, CDT entry increased and peaked at ∼60%; however, declines were observed within 6 months. In particular, although past research suggests that public reporting of individual performance might be an effective method to motivate provider behavior change, 30,31 this was not observed in our study. Instead, we observed that public auditing and reporting of attending-provider performance was associated with essentially static levels of CDT use.…”
Section: Discussioncontrasting
confidence: 91%
“…The application of clinical practice guidelines aims to improve the quality of healthcare and has direct benefits for patients and healthcare costs by reducing the probability of adverse effects, the damage resulting from additional tests, and the healthcare expenditure [9]. Hospital protocols are necessary, although it is also important to raise awareness about the benefits of supportive measures and the disadvantages of unnecessary pharmacological treatments through clinical sessions and other educational interventions [28,33]. Evaluation of modifications in clinical practice and patient outcomes after implementation of the protocol also acts as a key positive reinforcement for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports in the English literature showing a successful effort to decrease albuterol use, and most of these studies only showed an absolute reduction of albuterol use by 7% to 16% or a reduction occurring in the outpatient setting. 3,8,[11][12][13][14] Using a novel strategy of order set modifications, we were able to achieve absolute levels of bronchodilator use lower than the lowest rate of 33% reported in any previous inpatient work. Our order set intervention provides a more specific strategy for hospitals to adapt than a previous multicenter project.…”
Section: Discussionmentioning
confidence: 99%